2021
DOI: 10.5217/ir.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tobacco smoking on treatment choice and efficacy in inflammatory bowel disease

Abstract: horts. 3 It is well established that smoking significantly increases the risk of developing and worsens the disease course of CD, yet is protective against the development and reduces the severity of ulcerative colitis (UC). 4,5 However, what is less clear is whether smoking impacts the efficacy of therapeutics in IBD. Given the increased choice and availability of therapies with differing mechanisms of action, it may be surmised that for patients who continue smoking (i.e., failing efforts at cessation as is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…We found that the effect of smoking on the CD using the logistic regression model remained significant with an odds ratio ( OR ) of 2.319 (95% CI: 1.603, 3.485, p < 0.001), adjusting for sex, age, CD8 + T cells, CD4 + T cells, NK cells, B cells, monocytes, and granulocytes ( Table 2 ). The results suggested that smoking accelerated CD progression, which was consistent with previous reports ( Nicolaides et al, 2021 ; van der Sloot et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We found that the effect of smoking on the CD using the logistic regression model remained significant with an odds ratio ( OR ) of 2.319 (95% CI: 1.603, 3.485, p < 0.001), adjusting for sex, age, CD8 + T cells, CD4 + T cells, NK cells, B cells, monocytes, and granulocytes ( Table 2 ). The results suggested that smoking accelerated CD progression, which was consistent with previous reports ( Nicolaides et al, 2021 ; van der Sloot et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
“…Methylation marks are often considered potential mediators between exposures and outcomes. Numerous studies have established a clear relationship between smoking and the occurrence of IBD and its significantly detrimental effects on CD, whereas the opposite is the beneficial influence of the development of UC ( Tanja Birrenbach MUBM, 2004 ; Khasawneh et al, 2017 ; Nicolaides et al, 2021 ; van der Sloot et al, 2021 ). What is less clear is whether smoking impacts the biological mechanism in CD by mediating DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase is closely related to technological advances, improvements in health care and sanitation, increased energy utilization, modern transportation, changes in diet, and urbanization [17]. Smoking increases the risk of CD but is believed to reduce the severity of UC [59]. Smoking is associated with alterations in thiopurine metabolism and is considered to shorten the time to disease recurrence.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…26 , 27 In contrast to previous reports, neither smoking nor family history of IBD were associated with worse outcomes in the present study ( P >.05). 28 Cigarette smoking is a culturally sensitive topic. It may have been underreported.…”
Section: Discussionmentioning
confidence: 99%